Impact of lenalidomide-bortezomib-dexamethasone induction on patients with newly diagnosed multiple myeloma and renal impairment: Results from the Connect® MM Registry - Sikander Ailawadhi; Hans C. Lee; James Omel; Kathleen Toomey; James W. Hardin; Cristina J. Gasparetto; Sundar Jagannath; Robert M. Rifkin; Brian G. M. Durie; Mohit Narang; Howard R. Terebelo; Prashant Joshi; et al. (Blood Cancer Journal, 2024)
Abstract Limited data exist on the effects of induction treatment in patients with newly diagnosed multiple myeloma (NDMM) and renal impairment (RI), who may also be ineligible for autologous stem cell transplant. This analysis investigated the impact of lenalidomide-bortezomib-dexamethasone (RVd) induction on renal function in patients from the Connect® MM Registry based on transplant status. Eligible patients were aged ≥18 years with symptomatic MM diagnosed ≤2 months before enrollment. Patients in this analysis received front-line RVd for ≥3 cycles and were grouped by transplant status and baseline renal function. As of August 4, 2021, 344 transplanted and 289 non-transplanted patients had received RVd for ≥3 cycles at induction. Improved renal function was observed at 3, 6, and 12 months in patients with all severities of RI at baseline. In patients with >60 and ≤60 creatinine clearance mL/min at baseline, median progression-free survival was 49.4 months and 47.6 months in transplanted patients and 35.7 months and 29.1 months in non-transplanted patients, respectively. These results provide real-world evidence that patients with NDMM and RI who receive front-line RVd for ≥3 cycles may have improved renal function regardless of transplant status, with renal function no longer affecting the long-term outcome. Clinical trial information: NCT01081028.